Fihrist-i nuskhahā-yi khaṭṭi-yi Fārsi-yi Pākistān (Fihrist-i 8000 nuskha-yi khaṭṭi-yi kitābkhānahā-yi shakhṣī va dawlatī). Volume 1 : ʿUlūm-i Qurʾānī etc. - Nūshāhī, ʿĀrif, (Miras Maktoob, ISBN: 9789004365452., 2019)
This catalogue of Persian manuscripts in Pakistan was compiled by the well-known specialist of Islamic manuscripts ʿĀrif Nawshāhī (1955). It can be seen as a sequel to Aḥmad Munzawī's (d. 2015) 14-volume Fihrist-i mushtarak-i nuskhahā-yi khaṭṭi-yi Fārsi-yi Pākistān (1983-1997), besides Nawshāhī's own catalogues of the Persian manuscripts in the National Archives of Pakistan and the Punjab University Library in Lahore. The catalogue published here contains information on around 8000 manuscripts in 335 collections in Pakistan, mostly in non-government and private libraries, madrasas, and monasteries. In view of the threat of decay of manuscripts in private collections due to poor storage conditions and a declining interest in the Persian language, this catalogue is both a witness and a wake-up call. In this work, Nawshāhī relies on his own research, on notes by others, until then forgotten in the archives of the Iran-Pakistan Institute of Persian Studies in Islamabad, and also on different kinds of published sources. 4 vols; volume 1.